Original industrial gypsum-based lightweight high-strength concrete and preparation method thereof

By combining undisturbed industrial gypsum with a variety of lightweight materials, lightweight high-strength concrete with a low water-cement ratio and high strength is prepared, which solves the problems of low utilization rate of industrial gypsum and insufficient strength of super-sulfur cement, and achieves high efficiency and economy. of concrete preparation.

CN116640000BActive Publication Date: 2025-01-21WUHAN CHUTIANHAO BUILDING MATERIALS CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310634987.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-31
Publication Date
2025-01-21
Estimated Expiration
2043-05-31

AI Technical Summary

Technical Problem

In the prior art, the utilization rate of industrial gypsum is not high, and when producing premixed mortar and concrete, pretreatment increases costs and reduces efficiency, and the strength of supersulfur cement is difficult to meet the requirements of use.

Method used

Using undisturbed industrial gypsum as the base material, combined with phosphogypsum, mineral powder, cement, ceramic sand, ceramsite, zeolite powder and water-reducing agent, through three-level mixing of lightweight materials and modifiers, we can prepare a product with low water-cement ratio and high strength. of lightweight high-strength concrete.

Benefits of technology

It reduces the water-cement ratio and increases the strength of concrete, reaching a compressive strength of more than 65MPa, reducing water consumption, improving the density and later strength of concrete, and removing harmful impurities in industrial gypsum.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004259877710000091
    Figure BDA0004259877710000091
  • Figure BDA0004259877710000101
    Figure BDA0004259877710000101
Patent Text Reader

Abstract

The present invention proposes an original industrial gypsum-based lightweight high-strength concrete and a preparation method thereof, wherein the concrete mortar comprises phosphogypsum, mineral powder, cement, ceramic sand, ceramsite, zeolite powder, water reducer, modifier and water. The present invention adopts a three-graded combination of lightweight and water-absorbing materials, wherein high-strength ceramsite coarse aggregate, ceramic sand as fine aggregate, and zeolite powder as powder filler to prepare supersulfur concrete, and the final strength of the whole supersulfur concrete can reach more than 65MPa, which is far superior to the strength of traditional supersulfur concrete.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete, and in particular to an original industrial gypsum-based lightweight high-strength concrete and a preparation method thereof. Background Art

[0002] Phosphogypsum is an industrial byproduct of the phosphorus chemical industry. Every ton of phosphoric acid produced will produce about 3 to 5 tons of phosphogypsum. Desulfurized gypsum is a byproduct of desulfurization in the flue of coal-fired power plants, with nearly 100 million tons added each year. At present, the overall utilization rate of phosphogypsum and desulfurized gypsum is not high. Large-scale stacking will not only occupy a large amount of land resources, but also cause serious environmental problems. The current application of industrial gypsum is to make cement setting agent and gypsum building materials and roadbed materials. There are few studies on the application of industrial gypsum to produce ready-mixed mortar and ready-mixed concrete. According to existing data, most of them are first pre-treated by pulping, modification and aging of the original gypsum, and then used as a cementitious material in mortar and concrete. Pretreatment will increase costs and reduce efficiency.

[0003] Supersulfur gypsum slag cement is a ternary system cementitious material that mixes gypsum and slag cement clinker, also known as supersulfur cement. In recent years, due to the large output of industrial para-gypsum, the difficulty in utilization, and the easy secondary pollution, phosphogypsum and desulfurized gypsum have also become raw materials for the development of gypsum slag cement. Due to the hydration characteristics of supersulfur cement, it has high requirements for water-cement ratio, and the most suitable water-cement ratio is 0.4-0.42. If the water-cement ratio is too low, the water content of the hydration reaction of the slag in the later stage will be insufficient, and the strength development in the later stage will also be hindered; if the water-cement ratio is too high, its porosity will also be relatively high, resulting in a lower final strength. This characteristic also leads to the maximum strength of gypsum-slag cement being generally about 40MPa. For example, the invention patent with publication number CN109851308A discloses a phosphogypsum-based cement concrete with a water-cement ratio of 0.3 and a maximum compressive strength of 37.74MPa, which is difficult to meet the use requirements. Summary of the invention

[0004] In view of this, the present invention proposes an original industrial gypsum-based lightweight high-strength concrete with low water-cement ratio and high strength and a preparation method thereof.

[0005] The technical solution of the present invention is implemented as follows: On the one hand, the present invention provides an original industrial gypsum-based lightweight high-strength concrete, and the concrete mortar includes phosphogypsum, mineral powder, cement, ceramic sand, ceramsite, zeolite powder, water reducer and water.

[0006] On the basis of the above technical scheme, preferably, calculated by weight, the present invention provides 240-300 parts of phosphogypsum, 240-280 parts of mineral powder, 40-60 parts of cement, 400-500 parts of ceramic sand, 500-600 parts of ceramsite, 40-80 parts of zeolite powder, 0.8-1 part of water reducer and 135-165 parts of water.

[0007] On the basis of the above technical solution, preferably, it also includes 2 to 4 parts by weight of a phosphogypsum modifier, wherein the phosphogypsum modifier includes calcium oxide and polyferric sulfate.

[0008] Based on the above technical solution, preferably, the weight ratio of calcium oxide to polyferric sulfate is (1-2):1.

[0009] On the basis of the above technical solution, preferably, the phosphogypsum modification method is: phosphogypsum, phosphogypsum modifier and 1 / 3 to 1 / 2 parts by weight of water are mixed and pre-stirred for 3 to 5 minutes to obtain modified phosphogypsum.

[0010] Based on the above technical solution, preferably, the water-cement ratio is 0.22-0.24.

[0011] On the basis of the above technical solution, preferably, the particle size of the mineral powder is 10 to 15 μm.

[0012] On the basis of the above technical solution, preferably, the particle size of the ceramsite is 5 to 15 mm.

[0013] On the basis of the above technical solution, preferably, the particle size of the ceramic sand is 0.1-5 mm.

[0014] On the basis of the above technical solution, preferably, the water reducer is a polycarboxylic acid water reducer.

[0015] On the other hand, the present invention provides a method for preparing original industrial gypsum-based lightweight high-strength concrete, comprising the following steps:

[0016] S1, ceramsite and ceramic sand are soaked in water and then taken out to keep the surface dry;

[0017] S2, mixing expanded clay, ceramic sand, modified phosphogypsum, mineral powder, cement, zeolite powder, water reducer and remaining water, continuing to stir for 3 to 5 minutes, then pouring and vibrating to form, and curing under standard conditions after demoulding to obtain gypsum-based lightweight high-strength concrete.

[0018] The original industrial gypsum-based lightweight high-strength concrete and preparation method of the present invention have the following beneficial effects compared with the prior art:

[0019] (1) A three-grade combination of lightweight and water-absorbing materials is used to prepare ultrasulfur concrete, in which high-strength ceramsite coarse aggregate, ceramic sand is used as fine aggregate, and zeolite powder is used as powder filler. On the one hand, the combination of ceramsite, ceramic sand and zeolite powder can greatly reduce the bulk density of concrete and meet the requirements of lightweight concrete; on the other hand, the combination of three-grade water-absorbing materials can minimize the water consumption of concrete, make the internal structure of concrete more compact, and make the early strength development of concrete more rapid; at the same time, in the later stage of hydration, after the free water inside the slag cement is consumed, the free water inside the ceramsite and ceramic sand can diffuse outward to promote further hydration of the slurry, but the diffusion distance of free water in the aggregate is limited to a certain extent, so the internal curing effect of ceramsite and ceramic sand is more beneficial to the performance development of the interface transition slurry. By adding porous powder (zeolite powder), the slurry is evenly mixed after stirring, and its internal curing effect can act evenly on the entire slurry, thereby greatly improving the later strength of concrete. Through the mutual coordination of three-grade lightweight materials, the final strength of the entire supersulfur concrete can reach more than 65MPa, far exceeding the strength of traditional supersulfur concrete.

[0020] (2) Through modifiers, harmful impurities in industrial gypsum, such as phosphorus and fluorine, can be effectively removed, reducing their impact on the setting time and strength development of concrete.

[0021] (3) The present invention utilizes the water absorption and internal curing properties of the three-grade porous lightweight material to reduce the water-cement ratio of the concrete (the water-cement ratio is 0.22-0.24), improve the strength of the supersulfur concrete (above 65MPa), and prepare a lightweight (final apparent density 1750kg / m 3 )High strength concrete. DETAILED DESCRIPTION

[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] The particle size of the mineral powder used in the present invention is 10-15 μm, and the main raw material of the mineral powder is ground mineral powder, that is, ground water-quenched blast furnace slag powder, also known as slag micropowder. The particle size of ceramsite is 5-15 mm, and the particle size of ceramic sand is 0.1-5 mm, which is a mixture of materials with different particle sizes. The polycarboxylate water reducer is also known as polyether monomer HPEG-2400, which is purchased from Hubei Kewode Chemical Co., Ltd.

[0024] Example 1

[0025] The original industrial gypsum-based lightweight high-strength concrete of this embodiment, the concrete mortar includes 240kg of phosphogypsum, 240kg of mineral powder, 40kg of cement, 400kg of pottery sand, 500kg of ceramsite, 40kg of zeolite powder, 0.8kg of polycarboxylic acid water reducer and 135kg of water, and the water-cement ratio is 0.24.

[0026] The method for preparing concrete in this embodiment comprises the following steps:

[0027] S1, ceramsite and ceramic sand are soaked in water and then taken out to keep the surface dry;

[0028] S2, mix ceramsite, ceramic sand, phosphogypsum, mineral powder, cement, zeolite powder, water reducer and water, continue to stir for 3 minutes, then pour and vibrate to form, and after demolding, place it under standard conditions for curing to obtain gypsum-based lightweight high-strength concrete.

[0029] Example 2

[0030] The original industrial gypsum-based lightweight high-strength concrete of this embodiment, the concrete mortar includes 300kg of phosphogypsum, 280kg of mineral powder, 60kg of cement, 500kg of pottery sand, 600kg of ceramsite, 80kg of zeolite powder, 1kg of polycarboxylic acid water reducer and 165kg of water, and the water-cement ratio is 0.23.

[0031] The method for preparing concrete in this embodiment comprises the following steps:

[0032] S1, ceramsite and ceramic sand are soaked in water and then taken out to keep the surface dry;

[0033] S2, ceramsite, ceramic sand, phosphogypsum, mineral powder, cement, zeolite powder, water reducer and water are mixed, and the mixture is stirred for 5 minutes before pouring and vibrating to form the mixture. After demolding, the mixture is cured under standard conditions to obtain gypsum-based lightweight high-strength concrete.

[0034] Example 3

[0035] The original industrial gypsum-based lightweight high-strength concrete of this embodiment, the concrete mortar includes 280kg of phosphogypsum, 260kg of mineral powder, 50kg of cement, 450kg of ceramic sand, 550kg of ceramsite, 60kg of zeolite powder, 0.9kg of polycarboxylate water reducer and 140kg of water, and the water-cement ratio is 0.22.

[0036] The method for preparing concrete in this embodiment comprises the following steps:

[0037] S1, ceramsite and ceramic sand are soaked in water and then taken out to keep the surface dry;

[0038] S2, ceramsite, ceramic sand, phosphogypsum, mineral powder, cement, zeolite powder, water reducer and water are mixed, and the mixture is stirred for 4 minutes before pouring and vibrating to form the mixture. After demolding, the mixture is placed under standard conditions for curing to obtain gypsum-based lightweight high-strength concrete.

[0039] Example 4

[0040] The original industrial gypsum-based lightweight high-strength concrete of this embodiment, the concrete mortar includes 240kg of phosphogypsum, 240kg of mineral powder, 40kg of cement, 400kg of pottery sand, 500kg of ceramsite, 40kg of zeolite powder, 0.8kg of polycarboxylic acid water reducer and 135kg of water, as well as phosphogypsum modifiers: 1kg of calcium oxide and 1kg of polyferric sulfate, and the water-cement ratio is 0.24.

[0041] The method for modifying phosphogypsum is as follows: phosphogypsum, phosphogypsum modifier and 1 / 3 of water are mixed and pre-stirred for 3 minutes to obtain modified phosphogypsum.

[0042] The method for preparing concrete in this embodiment comprises the following steps:

[0043] S1, ceramsite and ceramic sand are soaked in water and then taken out to keep the surface dry;

[0044] S2, mix expanded clay, ceramic sand, modified phosphogypsum, mineral powder, cement, zeolite powder, water reducer and the remaining 2 / 3 of water, continue stirring for 3 minutes, then pour and vibrate to form, and after demolding, place it under standard conditions for curing to obtain gypsum-based lightweight high-strength concrete.

[0045] Example 5

[0046] The original industrial gypsum-based lightweight high-strength concrete of this embodiment, the concrete mortar includes 265kg of phosphogypsum, 270kg of mineral powder, 55kg of cement, 420kg of ceramic sand, 540kg of ceramsite, 70kg of zeolite powder, 1kg of polycarboxylic acid water reducer, 155kg of water, and phosphogypsum modifier: 2kg of calcium oxide and 1kg of polyferric sulfate, and the water-cement ratio is 0.23.

[0047] The modification method of phosphogypsum is as follows: phosphogypsum, a modifier and 1 / 2 of water are mixed and pre-stirred for 4 minutes to obtain modified phosphogypsum.

[0048] The method for preparing concrete in this embodiment comprises the following steps:

[0049] S1, ceramsite and ceramic sand are soaked in water and then taken out to keep the surface dry;

[0050] S2, mix ceramsite, ceramic sand, modified phosphogypsum, mineral powder, cement, zeolite powder, water reducer and the remaining 1 / 2 of water, continue stirring for 5 minutes, then pour and vibrate to form, and after demolding, place it under standard conditions for curing to obtain gypsum-based lightweight high-strength concrete.

[0051] Example 6

[0052] The original industrial gypsum-based lightweight high-strength concrete of this embodiment, the concrete mortar includes 288kg of phosphogypsum, 268kg of mineral powder, 48kg of cement, 465kg of ceramic sand, 585kg of ceramsite, 55kg of zeolite powder, 0.85kg of polycarboxylic acid water reducer, 148kg of water, and phosphogypsum modifier: 2kg of calcium oxide and 2kg of polyferric sulfate, and the water-cement ratio is 0.22.

[0053] The method for modifying phosphogypsum is as follows: phosphogypsum, a modifier and 1 / 3 of water are mixed and pre-stirred for 5 minutes to obtain modified phosphogypsum.

[0054] The method for preparing concrete in this embodiment comprises the following steps:

[0055] S1, ceramsite and ceramic sand are soaked in water and then taken out to keep the surface dry;

[0056] S2, mix ceramsite, ceramic sand, modified phosphogypsum, mineral powder, cement, zeolite powder, water reducer and the remaining 2 / 3 of water, continue to stir for 4 minutes, then pour and vibrate to form, and after demoulding, place it under standard conditions for curing to obtain gypsum-based lightweight high-strength concrete.

[0057] Example 7

[0058] The original industrial gypsum-based lightweight high-strength concrete of this embodiment, the concrete mortar includes 290kg of phosphogypsum, 255kg of mineral powder, 58kg of cement, 480kg of ceramic sand, 560kg of ceramsite, 75kg of zeolite powder, 0.88kg of polycarboxylic acid water reducer and 165kg of water, as well as phosphogypsum modifiers: 1.75kg of calcium oxide and 1.75kg of polyferric sulfate, and the water-cement ratio is 0.24.

[0059] The method for modifying phosphogypsum is as follows: phosphogypsum, a modifier and 1 / 2 of water are mixed and pre-stirred for 5 minutes to obtain modified phosphogypsum.

[0060] The method for preparing concrete in this embodiment comprises the following steps:

[0061] S1, ceramsite and ceramic sand are soaked in water and then taken out to keep the surface dry;

[0062] S2, mix ceramsite, ceramic sand, modified phosphogypsum, mineral powder, cement, zeolite powder, water reducer and the remaining 1 / 2 of water, continue stirring for 5 minutes, then pour and vibrate to form, and after demolding, place it under standard conditions for curing to obtain gypsum-based lightweight high-strength concrete.

[0063] Comparative Example 1

[0064] The difference between Comparative Example 1 and Example 1 is that the concrete mortar does not contain ceramsite and zeolite powder, the total amount of water is 125 kg, and the water-cement ratio is maintained at 0.24. The concrete mortar includes 240 kg of phosphogypsum, 240 kg of mineral powder, 40 kg of cement, 400 kg of ceramic sand, 0.8 kg of polycarboxylate water reducer and 125 kg of water.

[0065] Comparative Example 2

[0066] The difference between Comparative Example 2 and Example 1 is that the concrete mortar does not contain pottery sand and zeolite powder, the total amount of water is 125 kg, and the water-cement ratio is maintained at 0.24. The concrete mortar includes 240 kg of phosphogypsum, 240 kg of mineral powder, 40 kg of cement, 500 kg of ceramsite, 0.8 kg of polycarboxylate water reducer and 125 kg of water.

[0067] Comparative Example 3

[0068] The difference between Comparative Example 3 and Example 1 is that the concrete mortar does not contain ceramic sand and ceramsite, and the water-cement ratio is maintained at 0.24. The concrete mortar includes 240 kg of phosphogypsum, 240 kg of mineral powder, 40 kg of cement, 40 kg of zeolite powder, 0.8 kg of polycarboxylate water reducer and 135 kg of water.

[0069] Comparative Example 4

[0070] The difference between Comparative Example 4 and Example 1 is that the concrete mortar does not contain zeolite powder, the total amount of water is 125 kg, and the water-cement ratio is maintained at 0.24. The concrete mortar includes 240 kg of phosphogypsum, 240 kg of mineral powder, 40 kg of cement, 400 kg of ceramic sand, 500 kg of ceramsite, 0.8 kg of polycarboxylate water reducer and 125 kg of water.

[0071] Comparative Example 5

[0072] The difference between Comparative Example 5 and Example 1 is that the amount of water in the concrete mortar is increased to 170 kg, and the water-cement ratio reaches 0.3.

[0073] Comparative Example 6

[0074] The difference between Comparative Example 6 and Example 1 is that the amount of water in the concrete mortar is increased to 222 kg, and the water-cement ratio reaches 0.4.

[0075] Comparative Example 7

[0076] The difference between Comparative Example 7 and Example 1 is that fly ash is used to replace the zeolite powder in the concrete mortar.

[0077] Comparative Example 8

[0078] The difference between Comparative Example 8 and Example 1 is that the zeolite powder in the concrete mortar is replaced by silica fume.

[0079] Comparative Example 9

[0080] The difference between Comparative Example 9 and Example 4 is that it does not contain polyferric sulfate.

[0081] Concrete was prepared according to the methods in the embodiments and comparative examples, and its performance was tested by referring to the following methods: compressive strength: standard test blocks were made according to the method in GB / T50081-2002 "Standard for Test Methods for Mechanical Properties of Ordinary Concrete", and the compressive strength of the standard test blocks was measured after curing for 3d and 28d. The results are shown in Table 1.

[0082] Table 1 Concrete properties of the embodiments and comparative examples

[0083]

[0084]

[0085] As shown in Table 1, the water-cement ratio of the concrete prepared by the present invention is reduced to 0.22-0.24, and the concrete strength reaches above 65 MPa. After the phosphogypsum is modified, harmful impurities in the industrial gypsum are effectively removed, the setting time is shortened, and the strength of the concrete is also increased.

[0086] As shown in Comparative Examples 1 to 4, the strength of concrete will be reduced if any of the three-grade components are missing. As shown in Comparative Examples 5 to 6, increasing the water-cement ratio not only prolongs the setting time, but also reduces the strength of concrete. As shown in Comparative Examples 7 to 8, after adding fly ash, the strength is only 45.1MPa, because the activity of fly ash is lower than that of mineral powder, and the later strength is not as good as that of mineral powder. At the same time, since it has no internal curing effect, the growth effect on strength is not obvious. After adding silica ash, the strength can reach 58.3MPa. Since the silica ash has a small particle size, the filling effect is more obvious, the structure is more compact, and the silica ash is highly active, its later strength will increase to a certain extent. However, since silica ash has no internal curing effect, the hydration process of the slurry in the later stage is subject to certain restrictions, and the strength growth is also insufficient. As shown in Comparative Example 9, the lack of polyferric sulfate will reduce the strength of concrete.

[0087] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An original industrial gypsum-based lightweight high-strength concrete, characterized in that: Calculated by weight, the concrete includes 240-300 parts of phosphogypsum, 240-280 parts of mineral powder, 40-60 parts of cement, 400-500 parts of pottery sand, 500-600 parts of ceramsite, 40-80 parts of zeolite powder, 0.8-1 part of water reducer and 135-165 parts of water; the water-cement ratio is 0.22-0.24; It also includes 2 to 4 parts by weight of a phosphogypsum modifier, wherein the phosphogypsum modifier includes calcium oxide and polyferric sulfate, and the weight ratio of the calcium oxide to the polyferric sulfate is (1 to 2):1; The phosphogypsum modification method comprises: mixing phosphogypsum, a phosphogypsum modifier and 1 / 3 to 1 / 2 parts by weight of water and pre-stirring for 3 to 5 minutes to obtain modified phosphogypsum; The method for preparing original industrial gypsum-based lightweight high-strength concrete comprises the following steps: S1, ceramsite and ceramic sand are soaked in water and then taken out to keep the surface dry; S2, mixing expanded clay, ceramic sand, modified phosphogypsum, mineral powder, cement, zeolite powder, water reducer and remaining water, continuing to stir for 3 to 5 minutes, then pouring and vibrating to form, and curing under standard conditions after demoulding to obtain gypsum-based lightweight high-strength concrete.

2. The original industrial gypsum-based lightweight high-strength concrete according to claim 1, characterized in that: The particle size of the ceramsite is 5 to 15 mm.

3. The original industrial gypsum-based lightweight high-strength concrete according to claim 1, characterized in that: The particle size of the ceramic sand is 0.1-5 mm.

4. The original industrial gypsum-based lightweight high-strength concrete according to claim 1, characterized in that: The water reducer is a polycarboxylate water reducer.

Citation Information

Patent Citations

  • Phosphogypsum-based cement concrete mortar and preparation process thereof

    CN109851308A

  • Super sulfur cement

    CN104609748A

  • Low-shrinkage super-high strength concrete

    CN108929082A

  • Heat-insulated and heat-preserved concrete

    CN109053221A